Pengaruh Bioaktivator Pada Kotoran Ayam Dan Pemberian Trichoderma Terhadap Pertumbuhan Dan Hasil Kedelai (Glycine max L. Merril) - Andika Saputra; Fiana Podesta; Dwi Fitriani; Suryadi Suryadi; Ririn Harini (Pusat Penelitian dan Pengabdian pada Masyarakat Sekolah Tinggi Ilmu Pertanian Dharma Wacana, 2021)
Based on the research results, the effect of bioactivators on chicken manure and trichoderma on the growth and yield of soybeans (Glycine max L. Merril). showed a significant effect of manure fertilizers enriched with bioactivators on the height of soybean plants at the age of 28 DAS, 42 DAS, 56 DAS, number of leaves 28 DAS, 42 DAS, 56 DAS, number of branches 42 DAS, 56 DAS, plant wet weight, number of pods well, plant wet weight, plant dry weight, 100 seeds weight and seed weight per plant. but not significant effect on plant height 14 DAS, number of leaves 14 DAS, number of branches 28, root nodules, length of roots and pods of cipo. The treatment of chicken manure with bioactivators showed a significant increase which showed a significant effect on the observed parameters compared to standard NPK fertilizers. while the treatment of Trichoderma and the interaction between the two had a significant effect on the weight observation parameters of 100 seeds